PEMANFAATAN NEW MEDIA DALAM PROSES PEMBELAJARAN SELAMA MASA PANDEMI COVID-19 (Studi Kasus Pemanfaatan Whatsapp di SLB Kembar Karya Pembangunan 1 Jakarta Timur) - Afifah Dyah Pitaloka (2020)
The development of digital technology that is supported by the internet is very helpful in communication during the Covid-19 pandemic that was sweeping Indonesia since mid-March 2020. With this situation the government issued policies such as social distancing and large-scale social restrictions (PSBB). Such conditions require the community to remain at home, and carry out all activities such as work, worship, and study at home. This certainly has an impact on all levels of education which requires to undergo the learning process through online. The learning process through online or online is a new thing especially for special schools for children with special needs or what are called Extraordinary Schools. This study discusses the use of new media, especially the Whatsapp application conducted by the East Jakarta Twin School Development Teacher in the learning process with students with special needs to remain effective and implemented. The approach used in this research is descriptive qualitative case study research method obtained through interviews with several informants. The theory used in this research is Computer Mediated Communication (CMC) Theory.